A systematic review of the effectiveness of cognitive behavioral therapy in gambling disorder - Buran, Ayşe (Journal of Dependence, 2021)
Due to the increasing number of gambling disorders in recent years, various treatment methods have emerged by mental health professionals. Although various approaches address this problem, there are not many studies on the effectiveness of these approaches. The aim of this study is to investigate the effectiveness of cognitive behavioral therapy applied to gambling disorder in the literature. In this study using the PRISMA method, gambling disorder and cognitive behavioral therapy approaches were scanned in electronic databases and 10 studies were included in the systematic review. All studies used cognitive behavioral therapy (CBT) methods. There was no statistically significant difference between the CBT techniques used in the same study. All CBT approaches were found to be effective in the treatment of gambling, and were also effective in non-gambling secondary psychopathological problems. While the studies had a mean follow-up of 6 months, gambling shift behavior was generally observed in the first month of the therapy process. Even though all studies applied different methods, various solutions were provided to gambling disorder and secondary problems. The systematic reviews of studies on gambling disorder will provide more use of therapy methods especially in gambling disorder. In multidimensional examination and treatment of gambling disorder, not only psychopharmacological therapies but also eclectic approaches should be shaped with the addition of these approaches.
Keywords: Gambling disorder; addiction; cognitive behavioral psychotherapy